Traditional Islamic Education Institutions in Aceh - Mulia Rahman (Budapest International Research and Critics University, 2021)
Islamic education in Indonesia has been the main priority of the Indonesian Muslim community since the beginning of the development of Islam. This is in line with Islamic education activities in Indonesia which were born and grew in line with the development of Islam in Indonesia. In addition to the magnitude of the meaning of education, the importance of Islamization plays a very important role in encouraging Muslims to carry out Islamic teachings even though the system is simple and carried out informally. This is because the religion of Islam came to Indonesia brought by Muslim traders, while trading they broadcast the religion of Islam and whenever there was an opportunity they provided education and teachings of the Islamic religion. The emergence of meunasah, skeleton, Dayah as a traditional educational institution is closely related to the transfer of the education system from Madrasah Nizamiyah to the Aceh region which is combined with the government system so that a close relationship can be found between adat and religion. The education system in the reign of Sultan Iskandar Muda was a government program that was structured to take care of education. Based on the level and level of education in Aceh, it is known that Islamic educational institutions in the archipelago such as Meunasah (elementary level), Rangkang (junior secondary level), Dayah (upper secondary level), Dayah Teungku Chik (diploma level) and Jami'ah Bait al- Rahman (university level). As Islamic educational institutions in the archipelago, Rangrang, Meunasah and Dayah have different learning systems according to the level of scientific quality.